The genus Anathallis (Orchidaceae: Pleurothallidinae) in Mexico - Solano, Rodolfo; Licona, Ethian (Lankesteriana, 2023)
Anathallis encompasses nearly 120 species of neotropical orchids, with Mexico representing the northernmost limit of its distribution. During the current century, up to fifteen Mexican species have been classified in Anathallis. However, in recent years, several of them have been reclassified into Lankesteriana, Specklinia, and Stelis. Currently, Anathallis in Mexico includes A. greenwoodii, A. lewisiae, A. minutalis, A. oblanceolata, A. sertularioides, and A. yucatanensis. This work presents the taxonomic treatment for these species, the modeling of their potential distribution, and the assessment of their conservation status in Mexico. For this, specialized literature, living and herborized specimens, and online databases were examined. For each species, a description, drawing, photograph, and distribution map were prepared; additionally, information regarding nomenclature, habitat, phenology, comparison with similar species, and an assessment of its risk status is provided. Mexican Anathallis plants are characterized by their diminutive habit, rhizomatous growth, semi-open flowers with acute sepals and petals, free lateral sepals, mobile lip, and winged column. The genus includes five Mexican species: A. lewisiae, A. minutalis, A. oblanceolata, A. sertularioides, and A. yucatanensis. Anathallis greenwoodii exhibits a morphology more similar to Lankesteriana and it was transferred accordingly. Anathallis oblanceolata was previously known only from the type locality and is redescribed based on specimens previously confused with A. minutalis. Both species are endemic to the mountainous regions of Mexico. Anathallis lewisiae, A. sertularioides, and A. yucatanensis grow in warm, lowland areas along the Gulf of Mexico coast and Yucatan Peninsula. Lectotypes are designated here for Pleurothallis minutalis, P. tenuissima, and P. trichopoda.